1 - The Significance of HIV/AIDS for Universities in Africa - Michael J. Kelly, (Journal of Higher Education in Africa, 2003)
There are several reasons why universities in Africa should respond comprehensively to HIV/AIDS, but institutions across the continent are only slowly acknowledging these reasons. Despite the high prevalence of HIV/AIDS in the environments in which many universities operate, it does not appear that they have institutionalized a consistent response. Instead, there seems to be a tendency to treat the epidemic as a student or health issue, but not as something that must be integrated into a university’s core operations of reflecting on issues affecting society, teaching, research, and community engagement. The paper argues for a radical change in institutional focus that would allow the university to use its full potential to get ahead of HIV/AIDS, in its own ranks and in the world it serves. For such change to be realized, institutions must focus on developing dedicated high-level university leadership and total management commitment.